2013
DOI: 10.2174/1871527311312030007
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Microglial Activation in Immature Brains After Hypoxia- Ischemia

Abstract: In the present study, we tested whether the ongoing differentiation of microglia in the immature brain results in more robust microglial activation and pro-inflammatory responses than juvenile brains following hypoxia-ischemia (HI). Under normoxic conditions, microglial activation profiles were assessed in postnatal day 9 and postnatal day 30 mice (P9 and P30) by analyzing relative expression levels of CD45 in CD11b+/CD45+ microglia/macrophages. Flow cytometry analysis revealed that the hippocampi of P9 and P3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…Ipsilateral microglia counts were normalized to the counts in the corresponding contralateral hemisphere (IL/CL), ( Figure 1 ). At 2 days post-HI, HI induced a robust increase in microglia counts in the ipsilateral hippocampus of non-treated P9 mice (~ 9.5 fold), and less microglia proliferation in P30 hippocampus (~5.7 fold) ( Figure 1 A ), similar to what we reported previously(Ferrazzano, Chanana, 2013a). By comparison, in cortex and striatum the increase in ipsilateral microglial population in P9 and P30 at day 2 post-HI was comparatively modest (1.7 - 3.5 times) ( Figure 1 B, C ).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Ipsilateral microglia counts were normalized to the counts in the corresponding contralateral hemisphere (IL/CL), ( Figure 1 ). At 2 days post-HI, HI induced a robust increase in microglia counts in the ipsilateral hippocampus of non-treated P9 mice (~ 9.5 fold), and less microglia proliferation in P30 hippocampus (~5.7 fold) ( Figure 1 A ), similar to what we reported previously(Ferrazzano, Chanana, 2013a). By comparison, in cortex and striatum the increase in ipsilateral microglial population in P9 and P30 at day 2 post-HI was comparatively modest (1.7 - 3.5 times) ( Figure 1 B, C ).…”
Section: Resultssupporting
confidence: 90%
“…As previously described, CD45 expression can be used to characterize the activation state of microglia (Campanella et al, 2002, Denker et al, 2007, Ferrazzano, Chanana, 2013a, Stevens et al, 2002), where low signal is associated with quiescent microglia, medium intensity with activated microglia and high signal labeling blood-born monocytes. In the current study, less than 1% of the CD11b + /CD45 + population demonstrated CD45 high expression, similar to our prior studies(Ferrazzano, Chanana, 2013a). Figure 2 A-C, shows the percentage of CD45 medium activated microglia in P9 and P30 brains at day 2 and day 9 post-HI in hippocampus, cortex and striatum.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations